Effect of medium properties on the transport of cadmium in saturated porous medium. Issue 1 (1st January 2021) - Zhao, Younan; Jiang, Yanji; Kang, Runfeng; Chen, Menghua; Zhang, Zhe; Sun, Huimin; Wang, Nong
ABSTRACT: The presence of different soils composition complicates the transport behaviors of Cd(II) and thus makes it challenging to predict Cd(II) fate and transport. In this study, montmorillonite modified sand, humic acid modified sand and ferrihydrite modified sand were used as medium to explore the effect of modified sand content, pH and ionic strength (IS) on Cd(II) transport. The results revealed that the adsorption capacity of modified sand for Cd(II) was montmorillonite-coated sand>humic acid-coated sand>ferrihydrite-coated sand>quartz sand. While the increase of the coated sand content limited the transport ability of Cd(II) in sand columns. In addition, high IS and low pH promoted the mobility of Cd(II). The specific surface area, surface charge and adsorption sites of coated sand were the factors affecting the transport of Cd(II). This work provides new information on the transport and spread of Cd(II) in the soil and thus to better prevent Cd(II) from polluting the environment.